Microstructural organization of the layers of the rat cornea in norm - Slobodyan , O.M.; Rudnytska , Kh.I.; Simonov , V.F.; Hrytsenko , A.P.; Voytsenko , K.I. (Морфологія / Morphologia / Morfologìâ, 2024)
Actuality. From the above, today there is enough information in the domestic and foreign specialized literature about the structure of the retina at the micro level, but we decided to supplement and expand this issue thanks to our own research on the morphological organization of the layers of the cornea of ​​rats. Therefore, I believe that this study is relevant both from the point of view of experimental morphology and from a practical point of view. The aim of our research was a detailed study of the layered structure of the rat cornea in norm. Methods. The study was conducted on 15 sexually mature, purebred white male rats, weighing 120-130 g. 1 group of animals was used in our research: (15 animals) - intact. Before taking the material of the experimental site, the animal was removed from the experiment with the help of diethyl ether. The eyeballs of rats were used for microscopic examination (intersecting at the limbus area). Preparations for histological examination were prepared according to generally accepted methods. Results. According to our research, at the microstructural level of the cornea of ​​intact laboratory rats, a stratified squamos nonkeratinized epithelium (anterior epithelium), corneal stroma and endothelium (posterior corneal epithelium) are clearly visualized. The stratified squamous non-keratinized epithelium of the cornea in most areas forms 3-5 cell rows that form three main cell layers: basal, middle and superficial. The corneal stroma is thick, massive, formed by numerous clearly arranged connective tissue plates, with well-organized collagen matrix fibers. Descemet's membrane (posterior border plate) is located deeper, which covers the back surface of the cornea's stroma. Descemet's membrane, which contains collagen fibers and an amorphous substance, is the basal membrane of the posterior epithelium (endothelium) of the cornea. The posterior epithelium of the cornea (the endothelium of the anterior chamber of the eye) is preserved, represented by a single layer of flat cells that tightly adhere to Descemet's membrane and separate the posterior surface of the cornea from the vitreous fluid of the anterior chamber of the eye. In the future, these results will make it possible to create a micro-morphological basis of the norm in order to use it when comparing the changes that occur in the layers of the cornea during experimental modeling of the studied nosologies of various genesis. In the future, this will provide an opportunity to establish the most optimal period for correction and, as a result, stabilization of pathological effects.